972-P: Significant Weight Loss among People with Diabetes Despite Using Antidiabetic Medications Associated with Weight Gain after 90-Day Fitterfly Digital Therapeutics Program - PATANGE, SONALI A.; VERMA, RITIKA; SELVAN, CHITRA; KALRA, SANJAY; TIWASKAR, MANGESH H.; METHIL, VINOD; PATIL, BHAGYASHRI V.; MALDE, FORUM; NAIR, VINEET; JOSHI, SHILPA; SINGAL, ARBINDER K. (Diabetes (New York, N.Y.), 2023)
Background and Aim: Majority of people with Diabetes (PWD) use insulin and sulfonylurea (SU) as a necessary part of treatment regimen for glycemic control. Weight gain associated with these medications becomes a major challenge in effectively managing diabetes. The study evaluates the real-world effectiveness of the Fitterfly Diabetes program for weight management in PWD using antidiabetic medications associated with weight gain and weight loss. Methods: Deidentified data of 79 participants (mean age: 45.4 ± 10.4 years, female: 54.4 %) with T2DM enrolled in the program was analyzed. Out of all participants, 28 people used antidiabetic medications associated with weight gain (thiazolidinediones, meglitinides, SU, and insulin) while 51 participants used antidiabetic medications associated with weight loss (biguanides, sodium-glucose cotransporter-2 inhibitors). Participants using medications from both groups or any other antidiabetic medications were excluded. Data has been shown as the median (IQR). Results: After 90 days, participants using antidiabetic medications associated with weight loss showed reduction in HbA1c, weight, and waist circumference by -0.5 (-1.0, 1.0) %, -3.5 (-6.0, -1.1) kg, -5.0 (-9.0, -1.5) cm from the pre-program baseline of 7.6 (7.1, 8.4) %, 81.0 (68.0, 92.0) kg, and 105.0 (97.0, 110.0) cm respectively (P<0.001 for all). Participants using antidiabetic medications associated with weight gain showed reduction in HbA1c, weight and waist circumference by -1.3 (-2.8, -0.02) %, -2.0 (-3.6, 0.9) kg, -2.0 (-4.7, 0.0) cm from the baseline of 9.6 (8.1, 10.7) %, 73.0 (66.2, 79.4) kg, and 99.0 (92.0, 105.8) cm respectively (P<0.05 for all). Conclusion: Significant reduction in weight, HbA1c, and anthropometric parameters was observed after 90 days on the program irrespective of the effect of antidiabetic medications on weight. PWD looking to lose weight are good candidates for such programs.